The Effect of Using Instructional Media in Alef Education to Improve Listening Skills - Nuroh, Nuroh; Ubaidillah, Ubaidillah (Jurusan Pendidikan Bahasa Arab Fakultas Tarbiyah dan Keguruan Institut Agama Islam Negeri Sultan Maulana Hasanuddin, 2023)
This study aims to find out how the use of Alef Education learning media improves listening skills (a quasi-experimental study in class eleventh grade students in Islamic Senior High School 1 Kab. Serang) and the effect of using Alef Education learning media on improving listening skills (a quasi-experimental study in class eleventh grade student’ in Islamic Senior High School 1 Kab. Serang). Researchers use quantitative research methods using the quasi-experimental design and actual design experimental methods, namely experiment and control classes. The population of this study was 249 students of class eleven, and the sample used amounted to 36 students. The sampling technique used probably sampling with simple random sampling, which is a random sampling from the population because the population is considered homogeneous if the number of subjects is less than 100. The data collection methods used are observation, interview, documentation, pre-test, and post-test. The effect of using Alef Education learning is calculated from the pre-test and post-test with the arithmetic t-method > t-table 5,168 > 2,032. It can be concluded that there is an influence on listening skills in Alef Education learning.